Im[per]manências: estudos sobre desenho à luz dos manuais de pintura chineses - Basso, Aline (2020)
This thesis is a theoretical-practical reflection on the drawing. It grounds in light of the writings of two Chinese painting manuals. The first one is ‘The notes on the painting by Pumpkin Bitter Monk’, by monk Shitao. It was published in the early 18th century. The second is ‘The mustard seed garden: a manual of painting’, attributed by Wang An-chieh. Its first edition took place at the end of the 17th century. They refer to traditional painting and its rules. The Taoist, Buddhist and Confucian thinking structure them. They have a profoundly spiritual character and at the same time reflect a solid artistic practice theory. An incursion was made through these writings in this presented study and its accompanying drawings. It reflects the drawing in a theoretical way and as an artistic practice. From this, a theory was structured. It brought this look to contemporary Western thought about drawing. It was based essentially on the questions related to drawing as a process and also on the importance of looking at it as a procedural perspective. In this sense, this established the concept of Levels of Referencing the Real. It points out different ways of relating to the real during the development of a drawing. Throughout the investigation, Eastern and Western texts on art and design were analyzed and compared. Oriental philosophical texts were also consulted on the three currents of thought that structures the manuals. In parallel, artistic experimentation in drawing provided a deeper understanding of theoretical studies. Thus, new possibilities were revealed in terms of research and the theory itself. They pointed to the scope and multiplicity that can be achieved in a drawing process. The organization of the text took place based on Chinese pictorial thought. Especially in the three main moments: contemplation, gesture, and materiality. These themes are both synthesized in the manuals’ content. They also define some drawing guidelines in the West. The study and reflection of these issues resulted in the discussion presented in the last chapter. The guiding thread was the Buddhist concept of Impermanence. Under this principle, drawings were developed to constitute artistic research. They condense and legitimize the reflections elaborated throughout the thesis.